WORK-LIFE BALANCE AMONG WOMEN NURSING EMPLOYEES IN THE HEALTHCARE SECTOR; ROLE OF GENDER DISCRIMINATION AND ORGANIZATIONAL COMMITMENT WITH SPECIAL REFERENCE TO NORTH KERALA. - Sivaprasad. K and P. T. Raveendran (Int. J. Adv. Res., 2018)
Synchronous changes occurring in the pattern of work and family have impacted the work-life balance of individuals include nuclear families, single-parent families, and dual-earning parents, parents working at distant, different locations increasing household work in the current competitive scenario. Hence, balancing her work-related responsibilities and domestic responsibilities became difficult for women employees. So work-life balance of women employees‟ life has turned out to be a prominent topic in the society. Work-life balance refers to how effectively they divide their valuable time and effort in- between two important domains such as work and life, of every employee. The purpose of this study was to assess the role of Gender discrimination and the level of organizational commitment in maintaining the satisfactory level of work-life balance. Data were collected using the self-constructed questionnaire. Data analysis consisted of Descriptive statistics, ANOVA‟s, Crosstab, and also correlation to find the result. The finding suggested that the respondents were satisfied with their current level of work-life balance. They are very much committed to their organization, which is highly contributing towards work-life balance but results showed that there is the less significant relationship between gender discrimination and work-life balance. Suggestion is, more rigorous action would be needed to spread the appropriate awareness among the employees about work-life balance policies and plans and try to communicate those things in a proper way to the employees to prevent work-life imbalance issues and untoward treatment towards a particular gender.it will help the organization to improve their commitment level and also productivity with good maintenance of work-life balance among employees including women.